Muscle fitness to visceral fat ratio, metabolic syndrome and ideal cardiovascular health metrics (2019)
This study aimed to investigate the association between the muscle fitness to visceral fat level (MVF) ratio and the prevalence of metabolic syndrome (MetS) and ideal cardiovascular health (CVH) metrics among college students. A total of 1467 young adults recruited from the FUPRECOL study (Asociación de la Fuerza Prensil con Manifestaciones Tempranas de Riesgo Cardiovascular en Jóvenes y Adultos Colombianos), were categorized into four quartiles based on their MVF ratio. Muscular fitness was assessed using a digital handgrip dynamometer and visceral fat level was determined through bioelectrical impedance analysis. Ideal CVH was assessed, including lifestyle characteristics, anthropometry, blood pressure, and biochemical parameters. The body weight, waist circumference, body mass index (BMI), fat mass, fat mass index, and visceral fat level were significantly higher in subjects in Q1 (lower MVF ratio) than those in Q2, Q3, or Q4 (p less than 0.001). The muscle fitness (handgrip and normalized grip strength (NGS)) of the subjects in Q4 was significantly greater than that of those in Q1 to Q2 (p less than 0.001). Subjects with a medium-high MVF ratio (i.e., 3–4th quartiles) had an odds ratio of 2.103 of ideal CVH metrics after adjusting for age, gender, university, and alcohol intake (95% confidence interval (CI) 1.832 to 2.414; p less than 0.001). A lower MVF ratio is associated with worse CVH metrics and a higher prevalence of MetS in early adulthood, supporting the hypothesis that the MVF ratio could be used as a complementary screening tool that could help clinicians identify young adults with unfavorable levels of CVH and metabolic risk. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.